Grow Up Green: Edukasi Bercocok Tanam Bawang Prei melalui Media Botol Plastik di Sekolah Dasar - Shakira, Naila; Gaisani, Naila Jinan; Amani, Nailul; Mufidah, Khoirun Nisaul; Hanani, Fahriah Ismi; Ramadhani, Cindy Avika Fitria; Afriansyah, Muhammad Fahrul; Prayogi, Nanda; Cholil, Muhammad; Awi, Mohammad; Putra, Brayen Aji Pramana; Nugroho, Arya Vito; Kurniawan, Deddy (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service activity aims to increase environmental awareness and farming skills of elementary school students through the use of used plastic bottles as a growing medium for spring onions (Allium fistulosum L.). The program was implemented at SDN Gumuksari 01, Gumuksari Village, Kalisat District, Jember Regency, in August 2025, involving a total of 62 students in grades 4–6, but only ±40 students attended and participated in the entire series of practical activities. The method used was a participatory approach through the stages of preparation, implementation, evaluation, and follow-up. Evaluation was carried out through structured observations with a simple rubric (bottle cutting skills, number of aeration holes, depth of planting media) as well as reflection of student attitudes. The results of the activity showed active participation of students who attended with the output of ±40 units of planting media, filling 12 previously empty school pots, and positive changes in attitudes towards plastic waste management. Short-term impacts include increased technical farming skills, awareness of protecting the environment, and student motivation to plant at home. This activity provides novel value in integrating environmental education, waste management, and school-based food security with locally adapted green onions. Continued mentoring and integration of similar activities into the school curriculum or extracurricular activities are recommended.